Tingkat Kapasitas Masyarakat Pasca Bencana Gempa Bumi di Kota Palu (Studi Kasus: Kecamatan Palu Barat) - Maghfirah, Fitriah Fajar; Tyas, Wido Prananing (Universitas Diponegoro, Indonesia, 2020)
The Subdistrict of West Palu is one of the sub-districts in the City which is the center of social, government and trade activities. West Palu is also a center for the development of facilities and infrastructure in the City. This sub-district is not the most populated area in the city of Palu, but it is the most affected district and suffered the worst damage during the 28 September 2018 earthquake, that caused the loss of material and the number of fatalities. This study aims to understand the levels of community adaptation capacity of the earthquake in the Sub-district of West Palu. This study uses scoring and descriptive analysis to synthesize the results of the analysis by applying quantitative methods. Community adaptation capacity is seen from 4 (four) factors, which consist of financial support, community ability, supporting community, also technology and information. The results of the analysis indicate that the adaptation capacities level in the West Palu is at a moderate level. This shows that to survive and cope with the earthquake that will come at certain times, each family has strong ability and have been do their best to adapt, although it is not perfectly executed. The results of this study are expected to be input for the government and the community as disaster mitigationâ€™s effort for those who doing activities in earthquake prone areas in order to minimize the risk of earthquake disasters in the West Palu Sub district.Â